Diagnostic test accuracy of waist-to-height ratio as a screening tool for cardiovascular risk in children and adolescents: a meta-analysis - Fusheng Zhang; Yanbai Han; Hongli Wang; Yong Li; Zhiwei Yan (Taylor & Francis Group, 2022)
Context Waist-to-height ratio (WHtR) is a controversial evaluation index of cardiovascular risk factors (CVRFs) in children and adolescents. Objective To assess the accuracy of WHtR as a measure to screen for clusters of at least one CVRF (CVRF1), two CVRFs (CVRF2), and three CVRFs (CVRF3) in different ages, sexes, regions and cut-offs. Methods The PubMed, Web of Science, EBSCOhost, Springer, Taylor & Francis Online, Wiley Online Library, Wanfang, and CNKI databases were searched for eligible publications up to June 2021. The QUADAS-2 checklist was used to assess the methodology of the included studies. Results Twenty-two studies that evaluated 85281 children and adolescents aged 5-19 years were included in the meta-analysis. The AUSROC values were 0.56 (95% CI: 0.54-0.57), 0.82 (95% CI: 0.81-0.83), and 0.89 (95% CI: 0.89-0.90) for CVRF1, CVRF2, and CVRF3, respectively. Higher AUSROC values were found for adolescents (12-19 years), that is, 0.91 (95% CI: 0.88-0.93), 0.90 (95% CI: 0.87-0.92) for males, and 0.91 (95% CI: 0.90-0.91) for a cut-off of ≥ 0.51 in the identification of CVRF3. Conclusion WHtR can be used as an accurate screening tool for CVRF3 and CVRF2 in children and adolescents, and it is recommended to select different cut-offs according to different ages, sexes, and regions.